Hyaluronic acid–tumor necrosis factor-related apoptosis-inducing ligand conjugate for targeted treatment of liver fibrosis. (15th January 2015) - Yang, Jeong-A; Kong, Won Ho; Sung, Dong Kyung; Kim, Hyemin; Kim, Tae Hyung; Lee, Kang Choon; Hahn, Sei Kwang
Graphical abstract: Abstract: Liver fibrosis is a chronic liver disease caused by viral infection and/or metabolic, genetic and cholestatic disorders. The inhibition of hepatic stellate cell (HSC) activation and the selective apoptosis of activated HSCs can be a good strategy to treat liver fibrosis. The activated HSCs are known to be more susceptible to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) induced apoptosis than normal HSCs because death receptor 5 is overexpressed on the cell surface. In this work, a target-specific and long-acting hyaluronic acid (HA)–TRAIL conjugate was successfully developed for the treatment of liver fibrosis. The HA–TRAIL conjugate was synthesized by a coupling reaction between aldehyde-modified HA and the N-terminal amine group of TRAIL. The biological activity of the HA–TRAIL conjugate was confirmed by an in vitro anti-proliferation assay and caspase-3 expression in human colon cancer HCT116 cells. In vivo real-time bioimaging exhibited the target-specific delivery of near-infrared fluorescence dye-labeled HA–TRAIL conjugate to the liver in mice. According to pharmacokinetic analysis, the HA–TRAIL conjugate was detected for more than 4 days after single intravenous injection into Sprague–Dawley (SD) rats. Finally, we could confirm the antifibrotic effect of HA–TRAIL conjugate in an N -nitrosodimethylamine-induced liver fibrosis model SD rats.